2004
DOI: 10.1902/jop.2004.75.1.91
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Endothelial Growth Factor in Gingival Tissues and Crevicular Fluids of Diabetic and Healthy Periodontal Patients

Abstract: The results of this study showed that VEGF is increased in all periodontal tissues of both groups and in the healthy sites of diabetic patients. Additionally, GCF VEGF values increased in periodontal sites of all test groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
57
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(62 citation statements)
references
References 48 publications
4
57
1
Order By: Relevance
“…But they found statistically significant differences between periodontally healthy and unhealthy sites of these two groups, which is similar to Booth et al 18 Guneri's study indicated that the oral situation is more important than systemic disease for GCF mediators, because the VEGF levels in GCF were not different between periodontally healthy sites of diabetic patients and the control group. 17 This result indicates that oral hygiene may be one of the factors increasing VEGF that is unrelated to epilepsy.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…But they found statistically significant differences between periodontally healthy and unhealthy sites of these two groups, which is similar to Booth et al 18 Guneri's study indicated that the oral situation is more important than systemic disease for GCF mediators, because the VEGF levels in GCF were not different between periodontally healthy sites of diabetic patients and the control group. 17 This result indicates that oral hygiene may be one of the factors increasing VEGF that is unrelated to epilepsy.…”
Section: Discussionmentioning
confidence: 95%
“…27,28 Guneri et al investigated the VEGF concentration in GFC in patients with periodontal diseases. 17 Some of these patients (group I) had diabetic diseases, while the others (group II) were healthy without any systemic diseases. The differences of VEGF levels were found statistically insignificant between the periodontally healthy sites of these two groups and the negative control group.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In a previous study on biopsies obtained from patients with type 2 diabetes associated gingival overgrowth, we detected VEGF expression in keratinocytes from the basal and spinous layers and in many de novo capillaries (Pisoschi et al, 2009). Other authors reported increased VEGF expression in epithelial cells and endothelial cells in periodontitis-affected gingiva (Guneri et al, 2004;Keles et al, 2010;Lucarini et al, 2009). Giannobile et al (2003) suggested that VEGF could be an important growth factor for the onset of gingivitis and its progression to periodontitis.…”
Section: G) Vascular Endothelial Growth Factor (Vegf)mentioning
confidence: 88%
“…DM and periodontal disease are common chronic diseases in adults 22,23 . The general opinion is that there is no effect of gender on elevated blood glucose in diabetic patients, as noticed in this study, whereas both sexes were uniformly represented 24 .…”
Section: Discussionmentioning
confidence: 99%